Fabrication and Characterization of Capacitive RF MEMS Perforated Switch - K. Srinivasa Rao; Lakshmi Narayana Thalluri; Koushik Guha; K. Girija Sravani (IEEE Access, 2018)
In this paper, we have designed, simulated, fabricated, and characterized a clamped-clamped micro mechanical structure-based shunt capacitive RF MEMS switch. The clamped-clamped micromechanical structure is micromachined using a gold metal thickness of 500 nm. AlN is used as a dielectric material, and it is deposited using the dc sputtering PVD process. In the MEMS technology, particularly in devices fabrication, releasing the membrane is a difficult task, and here, we have presented a novel wet process to release the membrane. Primarily, the S1813 sacrificial layer is etched by using the piranha solution and cleaned with the IPA solution. Critical point drying is done after fabrication to reduce the stiction effect on the switch. Overall, the switch requires the pull-in voltage of 5.5 V for 1.8-μm displacement. In the process of optimization, primarily, the switch is designed and simulated using finite-element method tools. The reliability of the capacitive RF MEMS switches depends on the stiction problem caused by dielectric charging, and the proposed capacitive switch dielectric charging behavior is characterized using the CV curve method.